Handbook of phatophysiology - Lazenby, Ramona Browder (Wolters Kluwer/Lippincott Williams & Wilkins Health, 2011)
"This pathophysiology handbook is ideally suited for easy reference in the classroom or clinical environment. The book presents a summary of physiology concepts for each body system, followed by an overview of important pathophysiology concepts related to 'alterations' in that body system. These pathophysiology concepts provide the necessary foundation for understanding the disease or injury states that are presented next in the chapter"--Provided by publisher.